Implementing human factors in clinical practice. Issue 5 (14th March 2014) - Timmons, Stephen; Baxendale, Bryn; Buttery, Andrew; Miles, Giulia; Roe, Bridget; Browes, Simon
Abstract : Objectives: To understand whether aviation-derived human factors training is acceptable and useful to healthcare professionals. To understand whether and how healthcare professionals have been able to implement human factors approaches to patient safety in their own area of clinical practice. Methods: Qualitative, longitudinal study using semi-structured interviews and focus groups, of a multiprofessional group of UK NHS staff (from the emergency department and operating theatres) who have received aviation-derived human factors training. Results: The human factors training was evaluated positively, and thought to be both acceptable and relevant to practice. However, the staff found it harder to implement what they had learned in their own clinical areas, and this was principally attributed to features of the informal organisational cultures. Conclusions: In order to successfully apply human factors approaches in hospital, careful consideration needs to be given to the local context and informal culture of clinical practice.